A review of silver nanoparticle synthesis methods and their functional applications - Neonjyoti Bordoloi; Manash Pratim Sarma; Moja Kodak (Journal of Applied Pharmaceutical Research, 2026)
Background: The growing interest in the biosynthesis of nanoparticles, particularly silver nanoparticles (AgNPs), has gained massive attention due to their wide range of applications in electronics, biosensors, optics, catalysis, food, and environmental fields. Medical applications of AgNPs are mainly attributed to their substantial antimicrobial property and their relatively low toxicity under appropriate conditions. Plant extracts are more convenient, offering an eco-friendly, cost-effective approach that uses phytochemicals as natural reducing and stabilizing agents. However, a major gap is the lack of standardized synthesis techniques, leading to inconsistent nanoparticle properties and biological efficacy. Methodology: This review aims to provide a detailed study of the diverse synthesis routes of AgNPs and their applications. The study focuses on the impact of plant extract composition on other synthesis conditions. Characterization of nanoparticles is also discussed. Results and Discussion: Studies have shown that plant-derived AgNPs demonstrate better antimicrobial activity against various microorganisms, including bacteria and fungi. AgNPs synthesized from Ipomoea asarifolia exhibited strong antibacterial activity (IC₅₀ of 1 μg/mL) against bacterial pathogens. AgNPs produced using Cocos nucifera leaf extract showed significant antibacterial activity, with the highest activity against Citrobacter freundii (20 mm) and Pseudomonas aeruginosa (19 mm). AgNPs synthesized from Ricinus communis extracts remained stable at temperatures up to 100 °C and within a pH range of 5–6 for several months. Conclusion: The present review details the factors affecting the synthesis of AgNPs. Furthermore, it provides an overview of scalability challenges and the underlying molecular mechanisms in current research.